Education and practice belong together - The relevance of practice orientation in the (University) education of Social Workers and Social Pedagogues - Reinhard Gunsch; Karl Tragust (Social Work and Society)
In this paper the authors review the expectations of the"practice field" of the social services in Southern Tirol in the light of the"Recommendations for a university-based study programme for social work" (Empfehlungen zum universitären Studiengang für Soziale Arbeit), published by the"Autonomous Province of Bolzanoe". They stress the mutual relationship -e"give and take" - between the two learning areas (Lernfelder) i.e. the practice field and the university setting in the process of professional education and training of Social Workers and Social Pedagogues. In this context the"practice field" offers various means to the University in order to enhance the development of"Social Work" both as a professional activity and an academic discipline. Additionally the authors express their gratitude to Walter Lorenz and underline his contributions to and impact on the practice field in the region.